Transition based parser for telugu language - Nagaraju, G.; Mangathayaru, N.; Padmajarani, B. (International Journal of Engineering and Technology, 2018)
This paper explains transition dependency parsing approaches to build a dependency parser for Telugu language. Telugu treebank is given as an input to transition dependency parsers. One of the best transition dependency parser is the Malt parser. It is an independent system and it has nine methods to parse a sentence of any language. We have applied the treebank on all the methods of a Malt parser among which Arc-eager parser produces state-of-art results for Telugu language. Arc-eager method was produced LA (Label Accuracy) of 63%, UAS (Unlabeled Attachment Score) of 88.1% and LAS (Label Attachment Score) of 62.3%. In this paper we discuss a brief introduction of all Malt Parsing methods and an in detail explanation of Arc-eager dependency parsing.
Keywords: Dependency Parsing; Telugu Language; Transition Based Parsing; Malt Parser; Arc-Eager Parsing.